The Truth about Bullying: What Educators and Parents Must Know and Do - Urbanski, Jan; Permuth, Steve (Rowman & Littlefield Publishers, 2009)
The Truth About Bullying presents crucial information to assist educators and parents in creating a safe learning environment. This book is a practical guide to understanding what bullying is and the influence it has on a school. The who, what, when, where, and how of bullying are described in a clear manner that helps the reader to understand the myths and realities of bullying behavior. The latest trends in bullying, including hazing and contagion bullying, are presented, along with chapters dedicated specifically to cyberbullying and the special needs child. Recent research provides a foundation for readers as they learn how to address bullying and create a respectful, constructive school community. The authors address the importance of the school climate and culture and answer the question of whether a positive environment is enough to prevent bullying.